The Surgery of Celsus’ De Medicina - James W. Blatchford, III, MD (Annals of Surgery Open)
Celsus’ De Medicina (first century ce) is the first comprehensive treatise on medicine and surgery to survive from antiquity. Bridging the gap between the Hippocratic Corpus and the works of Galen, it documents the important advances in anatomy and surgery of the Alexandrian school during the Hellenistic era. De Medicina contains an anatomically based system of surgery and strikingly modern concepts of wound management, as well as the first accounts of hemostasis by ligature, per primam healing of wounds, amputation, and complex, elective operations, including lithotomy and inguinal herniotomy. The possibility (and desirability) of per primam healing, thereby permitting elective surgical procedures, was ignored until rediscovered in the 19th century; its recognition by Celsus prompts a re-evaluation of the excellence of ancient surgery.